Design and fabrication of copper-filled photonic crystal fiber for passive optical devices / Mohd Fahmi Azman - Mohd Fahmi , Azman (2019)
Sub-wavelength electromagnetic waves generated and confined along a metal-dielectric interface via polarized light excitation – also referred to as surface plasmon offers a unique possibility of guiding properties. In this thesis, the copper-filled photonic crystal fiber (PCF) as a new type of plasmonic waveguide is introduced. The holey structure of the photonic crystal fiber is exploited by incorporating a copper microwires into one of the air holes of the PCF. Initially, a technique to fabricate copper encapsulated by silica is developed. By adopting the fiber drawing method, we combine the traditional Taylor wire process to fabricate such structure. We chose Taylor wire process because it is one of the most practical ways and the suitability of the facility that we have. This technique provides a desired copper-in-glass structure with excellent controls over the aspect ratio, diameter, and length. We successfully fabricated a copper-core optical fiber that extends for 100’s of meters while remaining up to 6 meters long electrically continuous the longest metal in glass-based fiber reported so far. This technique ensures high repeatability and mass-productions of ultra-long metal in glass, and opens the possibility of nano-sized copper wires resulting in plasmon based applications. Metallic PCF has many applications in the field of optics communications, especially in passive optical device. Thus, by employing the copper-cane format, we could produce a copper-filled PCF. A traditional approach of stack-and-draw method is used to fabricate copper-filled PCF. We designed a single copper wire which was placed next to the PCF core. The light propagated in the fiber core eventually couple to the SPPs mode, generated by the copper at the phase matching wavelength, also known as resonant condition. The results suggested a high loss occurred at the phase matching condition. The coupled mode theory was numerically analyzed to investigate the dispersion properties and loss of the proposed structured. It was found that the fabricated copper-filled PCF showing the good properties as a polarization filter with high attenuation, a narrow full-half width maximum (FHWM), high crosstalk and significant bandwidth .Taken together, the PCF polarization filter can also work in the communication wavelength of 1.31 μm and 1.55 μm when the diameter of the copper is altered. This study enables the realization of wavelength-dependent polarization filter. Next, we also proposed a polarization splitter based on copper-filled dual core photonic crystal fiber. The copper wire is placed between the PCFs cores. We numerically analyze the proposed dual-core structure with commercially available software, COMSOL Multiphysics. Copper wire will increase the birefringence of the PCF structure thus would result in shorter coupling length between both cores. Short coupling length is one of the key parameter as a good splitter. The coupling length for the proposed structure is 1196 μm with coupling ratio of 2 which could operate at 1.55 μm, the communication band. Plus, the extinction ratio for the copper-filled dual-core PCF is considerably low at 1.55 μm with -40 dB. The bandwidth achieved with extinction ratio lower than -20 dB is 88 nm – realizing a broadband and single splitting device which operates at 1.55 μm.